Elevated CO2 decreases micronutrient Zn but not Fe in vegetables – evidence from a meta-analysis - Wang, Xiaolin; Zhang, Shengmin; Li, Haichao; Du Laing, Gijs; Odlare, Monica; Skvaril, Jan (Frontiers in Plant Science, 2025)
With carbon dioxide (CO2) levels continuing to rise in the coming decades and threatening agro-ecosystems worldwide, it is crucial to understand the impact of elevated CO2 on global food production and security. Elevated CO2 levels have been found to reduce micronutrients such as Zinc (Zn) and Iron (Fe) in staple crops, potentially exacerbating the already existing global micronutrient deficiency issue. However, as vegetables serve as another key source of micronutrients, it remains uncertain to what extent this negative effect on micronutrient levels also applies to them. To address this, we investigated the effects of elevated CO2 on Zn and Fe in vegetables using a meta-analysis. As expected, we found a significant increase (27%, 95% CI: 14–41%) in vegetable biomass production under elevated CO2 levels. Elevated CO2 (i) significantly reduced overall Zn concentration in vegetables by 8.9% (95% CI: 4–14%), while this effect was pronounced only in fruit vegetables (11%), but not in leafy and stem vegetables; (ii) consistently exhibited minimal effects on Fe concentration in vegetables. In the context of climate change with rising CO2 levels, these findings suggest that elevated CO2 could potentially exacerbate Zn deficiencies through vegetable consumption, albeit with enhanced vegetable yields. Furthermore, as the global population increasingly adopts vegetarian diets in the future, these results underscore the need for mitigation strategies to address potential future micronutrient deficiencies.